MOTIF INDONESIA MEMBAHAS INCLUSIVE DIGITAL ECONOMY ACCELERATOR HUB (IDEA HUB) DALAM KONFERENSI TINGKAT TINGGI (KTT) G-20 DI OSAKA 2019 - Harra Fisabilillah; Yessi Olivia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study analyzes Indonesia's motives for bringing the Inclusive Digital Economy Accelerator Hub (IDEA Hub) proposal which was presented at the G-20 Summit in Osaka in 2019. IDEA Hub is a digital repository platform that contains information on digital economy business models whose economic activities use online connections. connections). Indonesia is a country that has great potential for the advancement of the digital economy, one of which is through electronic commerce (e-commerce) which has a positive impact on businesses and consumers. However, when compared to other G20 countries, Indonesia cannot be said to be advanced in its digital economy. Therefore, Indonesia is trying to develop a digital economy through the IDEA Hub proposal submitted by President Joko Widodo at the 2019 G20 Summit in Japan which was held on 28 29 June 2019. This study uses quantitative methods, with descriptive analysis through literature studies sourced from several books, journals, articles, websites. This research uses the perspective of Independent Liberalism and International Cooperation Theory. The results of this study indicate that Indonesia shows a positive response in the development of the digital economy. Through the IDEA Hub proposal, according to the Osaka 2019 full compliance report, Indonesia has fully fulfilled its commitment to increase interoperability of various national and international frameworks. Bank Indonesia launched a standard quick response code (QR) used as payment through e-money applications, electronic wallets, and mobile banking known as the QR Code Indonesian Standard (QRIS), and also Bank Indonesia issued a blueprint entitled Bank Indonesia: Navigating the System National Payments in the Digital Era, as a follow-up to the Indonesia Payment System Vision 2025. Bank Indonesia is also cooperating with Banko Sentral ng Pilipinas to enhance cooperation in improving payment systems and digital financial innovation. Keywords: Motive, Inclusive Digital Economy Accelerator Hub, G-20 Summit, Digital Economy